Guiding Brain‐Tumor Surgery via Blood–Brain‐Barrier‐Permeable Gold Nanoprobes with Acid‐Triggered MRI/SERRS Signals. Issue 21 (15th March 2017) - Gao, Xihui; Yue, Qi; Liu, Zining; Ke, Mengjing; Zhou, Xingyu; Li, Sihan; Zhang, Jianping; Zhang, Ren; Chen, Liang; Mao, Ying; Li, Cong
Abstract : Surgical resection is a mainstay in the treatment of malignant brain tumors. Surgeons, however, face great challenges in distinguishing tumor margins due to their infiltrated nature. Here, a pair of gold nanoprobes that enter a brain tumor by crossing the blood–brain barrier is developed. The acidic tumor environment triggers their assembly with the concomitant activation of both magnetic resonance (MR) and surface‐enhanced resonance Raman spectroscopy (SERRS) signals. While the bulky aggregates continuously trap into the tumor interstitium, the intact nanoprobes in normal brain tissue can be transported back into the blood stream in a timely manner. Experimental results show that physiological acidity triggers nanoparticle assembly by forming 3D spherical nanoclusters with remarkable MR and SERRS signal enhancements. The nanoprobes not only preoperatively define orthotopic glioblastoma xenografts by magnetic resonance imaging (MRI) with high sensitivity and durability in vivo, but also intraoperatively guide tumor excision with the assistance of a handheld Raman scanner. Microscopy studies verify the precisely demarcated tumor margin marked by the assembled nanoprobes. Taking advantage of the nanoprobes' rapid excretion rate and the extracellular acidification as a hallmark of solid tumors, these nanoprobes are promising in improving brain‐tumor surgical outcome with high specificity, safety, and universality. Abstract : Gold nanoprobes are developed to guide brain‐tumor surgery by crossing the blood–brain barrier. Assembly of the nanoprobes in the acidic tumor extracellular fluid triggers the activation of both the magnetic resonance signal for preoperatively defining the tumor margins and the surface‐enhanced resonance Raman spectroscopy signal for intraoperatively guiding the tumor surgery. These nanoprobes are promising candidates to improve the outcome of brain‐tumor surgery.